THE USE OF PUPPET IN STORYTELLING TO IMPROVE STUDENTS' SPEAKING SKILLS - Faula Nisa Aulia, Faula (2020)
This study aims to find out how the use of puppet in storytelling could improve students' speaking skills. The subject of this research were students of one class of a Junior High School in Bandung. This particular research is categorized as one group pre-test and post-test experimental design. The data were collected by using three instruments including; pre-test, post-test, and interview. The findings of this study are that the use of puppet in storytelling can improve students' speaking skills and students' perception in using puppet as learning media. The results showed that there was an improvement in students' speaking skills in several aspects, such as pronunciation, grammatical accuracy, vocabulary, fluency, and interactive communication. The mean obtained during the study in pre-test 48 and post-test 79. Students become more confident and enthusiastic to speak English in the classroom. Then, it makes to intensively participate in speaking English and get more opportunities to have produced performance by storytelling using expressions adjusting to their respective roles in the use of puppet. Keywords: Puppet, Storytelling, Speaking Skills, Students. Penelitian ini bertujuan untuk mengetahui bagaimana penggunaan boneka wayang dalam bercerita dapat meningkatkan keterampilan berbicara siswa. Subjek penelitian ini adalah siswa dari satu kelas di SMP di Bandung. Penelitian khusus ini dikategorikan sebagai satu kelompok pre-test dan post-test eksperimen desain. Data dikumpulkan dengan menggunakan tiga instrumen termasuk; pre-test, post-test, dan wawancara. Temuan dari penelitian ini bahwa penggunaan boneka wayang dalam bercerita dapat meningkatkan keterampilan berbicara siswa dan persepsi siswa dalam menggunakan boneka wayang sebagai media pembelajaran. Hasil penelitian ini menunjukkan bahwa adanya peningkatan keterampilan berbicara siswa dalam beberapa aspek, seperti pengucapan, akurasi tata bahasa, kosa kata, kelancaran, dan komunikasi interaktif Nilai rata-rata yang diperoleh selama penelitian pada pre-test 48 dan post-test 79. Siswa menjadi lebih percaya diri dan antusias untuk berbicara bahasa Inggris di kelas. Kemudian, membuat siswa untuk berpartisipasi secara intensif dalam berbicara bahasa Inggris dan mendapatkan lebih banyak kesempatan untuk menghasilkan kinerja dengan mendongeng menggunakan ekspresi menyesuaikan dengan peran masing-masing dalam penggunaan boneka. Kata kunci: Boneka Wayang, Mendongeng, Keterampilan Berbicara, Siswa.